2019
DOI: 10.1111/anu.13014
|View full text |Cite
|
Sign up to set email alerts
|

Optimum selenium requirement of juvenile Nile tilapia, Oreochromis niloticus

Abstract: A feeding experiment was conducted to determine the optimum selenium requirement in juvenile Nile tilapia. Each of six purified diets with Se‐methionine levels at 0.05, 0.21, 0.41, 0.57, 0.79 and 1.00 mg/kg was assayed in triplicate with initial body weight of 3.00 ± 0.01 g for 8 weeks. The growth of fish was obviously increased when the dietary Se was less than 0.57 mg/kg diet and reached a plateau when the dietary Se was ≥0.57 mg/kg. Serum and hepatopancreatic glutathione peroxidase (GPx) activity increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Unlike other micronutrients, gross deficiency of Se alone has not been characterized due to its interaction with vitamin E, polyunsaturated fatty acids and other dietary factors. Early clinical signs of deficiency caused by low dietary intake of Se have been detected in low enzyme activities in plasma and liver glutathione peroxidase of several fish species [ 145 , 146 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 180 , 181 ]. Selenium deficiency led to reduced growth in rainbow trout [ 146 ], carp [ 182 ] and catfish [ 170 ], but Se deprivation did not lead to any pathological signs in these species.…”
Section: Micromineralsmentioning
confidence: 99%
“…Unlike other micronutrients, gross deficiency of Se alone has not been characterized due to its interaction with vitamin E, polyunsaturated fatty acids and other dietary factors. Early clinical signs of deficiency caused by low dietary intake of Se have been detected in low enzyme activities in plasma and liver glutathione peroxidase of several fish species [ 145 , 146 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 180 , 181 ]. Selenium deficiency led to reduced growth in rainbow trout [ 146 ], carp [ 182 ] and catfish [ 170 ], but Se deprivation did not lead to any pathological signs in these species.…”
Section: Micromineralsmentioning
confidence: 99%
“…Selenium is an essential element in nutrition; it is the major component of selenoprotein, which is important for antioxidative stress mechanisms, thyroid hormone metabolism, and immune responses [ 96 ]. Ning et al [ 97 ] showed that the dietary supplementation of selenium at 570 ppb could enhance weight gain and increase hepatopancreatic and serum selenium levels in juvenile Nile tilapia, depending on glutathione peroxidase activities. Accordingly, this supplementation rate is recommended for juvenile Nile tilapia.…”
Section: Resultsmentioning
confidence: 99%